Focus of attention changes intracortical excitability in the primary motor cortex. - Marinovic, Welber (2016)
New evidence recently published in Acta Physiologica shows that the focus of attention - internal or external - during execution of a motor task can cause transient neuroplastic-like responses in motor areas of the brain (Khun et al., 2016). Neuroplasticity refers to the capacity of the brain to reorganize itself in response to experience. Typically, changes to the organization of the brain come about to support brain function. For instance, after a spinal cord injury or stroke, the brain must adapt to allow functional recovery (Rao et al., 2016). The recognition that the brain must change to improve function has led to several attempts to boost neuroplasticity. Non-invasive brain stimulation techniques such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) not only allow one to directly modulate neuroplasticity, but also provide a window for examining the mechanisms supporting brain functions. Unsurprisingly, there has been an explosion in the number of studies using these methods to study our ability to (re)learn or adapt to improve motor function (Kang et al., 2016). This article is protected by copyright. All rights reserved.